Plant-based scaffolds and osteogenesis: a systematic review - Gul , Hashmat; Kunza Naveed Asdaq; Muhammad Kaleem; Malik, Muhammad Hashim (Journal of the Pakistan Medical Association, 2024)
Objective: To enhance the understanding and usefulness of decellularised plant tissues as scaffolds for bone tissue engineering, and to review the recent advances in plant-based scaffolds for bone regeneration. Method: The systematic review was conducted from February to June 2022, and comprised literature search on PubMed and Science Direct databases for articles published in the English language between 2013 and June, 2022. The search was conducted using key words ‘plant-based scaffolds and osteogenesis’ and ‘decellularised plant and scaffolds and bone tissue engineering’ and ‘plant root-based scaffold and bone formation’. Full-text articles and short communication covering both in vitro and in vivo studies focussing on plant-based scaffolds for osteogenesis were included. Additional references that satisfied the inclusion criteria were found on Google Scholar and included in the review. Quality evaluation of the studies included was done independently by two researchers, and the risk of bias was calculated and categorised as low, medium and high risk. Results: Of the 564 articles, 10(1.77 %) were included; 6(60%) purely in vitro studies, and 4(40%) studies having both in vitro and in vivo components. Decellularized plant tissue alone was used as three-dimensional scaffold materials in 5(50%) studies, but in 4(40%) studies, plant-based composite scaffolds were used. The risk of bias was medium in 7(70%) studies. Conclusions: Plant-based scaffolds promote osteogenesis, but more in vivo research on plant-based studies is needed to label it as suitable scaffolds for bone tissue engineering. Key Words: Plant-based scaffolds, Osteogenesis, Decellularised Plant, bone tissue engineering, Plant root-based scaffold, Bone formation.